Theatre censorship in Spain, 1931-1985 - O'Leary, Catherine, 1971-; Thompson, Michael, 1957- (Iberian and Latin American studies., 2023)
This is a comprehensive study of the impact of censorship on theatre in twentieth-century Spain, analysing changes in censorship from the Second Republic to the post-Franco transition to democracy, and illuminating the ideological underpinnings, the effects on the industry and the responses of theatremakers.